Special Economic Zones and WTO Compliance: Evidence from the Dominican Republic. (14th June 2018) - Defever, Fabrice; Reyes, José‐Daniel; Riaño, Alejandro; Sánchez‐Martín, Miguel Eduardo
Abstract : Special economic zones (SEZ), one of the most important instruments of industrial policy used in developing countries, often impose export share requirements (ESR). That is, firms located in SEZ are required to export more than a certain share of their output to enjoy a wide array of incentives—a practice prohibited by the World Trade Organization (WTO) Agreement on Subsidies and Countervailing Measures. In this paper we exploit the staggered removal of ESR across products and over time in the SEZ of the Dominican Republic—a reform driven by external commitments to comply with WTO disciplines on subsidies—to evaluate how ESR affect export performance at the product and firm levels. Using customs data on international trade transactions from the period 2006 to 2014, we find that making the Dominican SEZ regime WTO‐compliant made SEZ more attractive locations for exporters to be based in. The reform, however, did not have a significant effect on the country's exports or on the share of export value originating from SEZ.